Dislodged Levornogestrel-intrauterine system intra-abdominally without uterine perforation: is it possible? - Ng, Beng Kwang; Lim, Pei Shan; Shahizon Azura Mohamed Mukari; Ng, YL; Shafiee MN; Mohd Hashim Omar (Faculty of Medicine, UKM Medical Centre, 2016)
We report a case of dislodged Levornogestrel-intrauterine system (LNG-IUS, Mirena®) without evidence of uterine perforation. A 37-year-old Para 4+1presented with 3 months history of lower abdominal pain. Examination and imaging showed that the device was not present in the uterine cavity. She underwent laparoscopic retrieval of Mirena®. There was no evidence of uterine perforation intra-operatively. This case illustrated the rare possibility of dislodged Mirena®intra-abdominally without evidence of uterine perforation. The management for missing IUS was reviewed.